Multi-hop wireless command and telemetry communication system for remote operation of robots with extending operation area beyond line-of-sight using 920 MHz/169 MHz. (2nd June 2020) - Kagawa, Toshinori; Ono, Fumie; Shan, Lin; Miura, Ryu; Nakadai, Kazuhiro; Hoshiba, Kotaro; Kumon, Makoto; Okuno, Hiroshi G.; Kato, Shin; Kojima, Fumihide
Abstract : The role of robot technologies is growing particularly in the areas of disaster response, infrastructure inspection, and so on. For remote operation of the robots, wireless communication is important to control, send command, and receive telemetry signals. However, it could be often disconnected due to radio wave attenuation, shadowing, or interference in the real field. In order to overcome the above problems, we have proposed and developed a multi-hop communication technology, specialized for remotely controlled robots, including drones, with high reliability and low latency using dual frequency band in 920 and 169 MHz. In this paper, we evaluate the radio propagation and communication quality characteristics in field experiment. In the experiment, the application of the proposed technology to disaster response was demonstrated. GRAPHICAL ABSTRACT: UF0001